Deformation and Heat Transfer on Three Sides Protected Beams under Fire Accident - Imran, M. (Institute of Physics Publishing, 2018)
Fire accidents are common in oil and gas industry. The application of passive fire protection (PFP) is a costly solution. The PFP is applied only on critical structural members to optimise project cost. In some cases, beams cannot be protected from the top flange in order to accommodate for the placement of pipe supports and grating. It is important to understand the thermal and mechanical response of beam under such condition. This paper discusses the response of steel beam under ISO 834 fire protected, unprotected and three sides protected beams. The model validated against an experimental study. The experimental study has shown good agreement with FE model. The study revealed that the beams protected from three sides heat-up faster compare to fully protected beam showing different temperature gradient. However, the affects load carrying capacity are insignificant under ISO 834 fire. Â© 2018 Published under licence by IOP Publishing Ltd.